EKSTRAKSI PARAMETER ELEKTRONIK SEL SURYA ORGANIK DENGAN MODEL ELEKTRONIK DUA DIODA - Sesa, Elisa; Ulum, Syahrul; Darwis, Darmawati (Univ. Tadulako, 2014)
The organic photovoltaic cells (OPV) characteristics depend on several factors, i.e.: device structure, morphology of the active layer, and the active materials.These characteristic can be varied due to the applied treatment in the fabrication. The characteristic variations of OPV can be observed through the electrical parameters. These parameters can be extracted from the I-V curve. The purpose of this paper is to show that the two-diode model accurately extract the electrical parameters of several I-V curves comparing to the one-diode model. The model is built using the MATLAB program. The simulation results is given the average correlation value (R2) is 0.999 which shows that the extracted electrical parameters is valid to be used in the further analysis.